2018
DOI: 10.1037/emo0000359
|View full text |Cite
|
Sign up to set email alerts
|

Disgust sensitivity is primarily associated with purity-based moral judgments.

Abstract: Individual differences in disgust sensitivity are associated with a range of judgments and attitudes related to the moral domain. Some perspectives suggest that the association between disgust sensitivity and moral judgments will be equally strong across all moral domains (i.e., purity, authority, loyalty, care, fairness, and liberty). Other perspectives predict that disgust sensitivity is primarily associated with judgments of specific moral domains (e.g., primarily purity). However, no study has systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 80 publications
9
78
2
2
Order By: Relevance
“…In other work on moral decision making (Wagemans, Brandt, & Zeelenberg, 2017), similar issues were tackled by using a well-validated measure of moral judgment including a wide range of moral judgments. Prior work made it difficult to test if emotions had specific From the Political Here and Now to Generalizable Knowledge 7 relationships with moral judgments in specific moral domains or across many moral domains, because research used unstandardized and ad hoc measures of moral judgments covering limited portions of the moral domain (e.g., Cheng, Ottati, & Price, 2013;Horberg, Oveis, Keltner, & Cohen, 2009).…”
Section: Representative Political Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other work on moral decision making (Wagemans, Brandt, & Zeelenberg, 2017), similar issues were tackled by using a well-validated measure of moral judgment including a wide range of moral judgments. Prior work made it difficult to test if emotions had specific From the Political Here and Now to Generalizable Knowledge 7 relationships with moral judgments in specific moral domains or across many moral domains, because research used unstandardized and ad hoc measures of moral judgments covering limited portions of the moral domain (e.g., Cheng, Ottati, & Price, 2013;Horberg, Oveis, Keltner, & Cohen, 2009).…”
Section: Representative Political Systemsmentioning
confidence: 99%
“…Prior work made it difficult to test if emotions had specific From the Political Here and Now to Generalizable Knowledge 7 relationships with moral judgments in specific moral domains or across many moral domains, because research used unstandardized and ad hoc measures of moral judgments covering limited portions of the moral domain (e.g., Cheng, Ottati, & Price, 2013;Horberg, Oveis, Keltner, & Cohen, 2009). By using a validated measure that spanned many moral domains (Clifford, Iyengar, Cabeza, & Sinnott Armstrong, et al, 2015) we were able to test if disgust sensitivity predicted harsher moral judgments across domains or were specific to a particular domain (Wagemans et al, 2017). We found that disgust sensitivity was more strongly related to judgments in the purity domain than any of the other moral domains.…”
Section: Representative Political Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…So konnten Wagemans et al [2018] Wir vermuten zudem, dass es einen Zusammenhang zwischen den Ekelkonstrukten und der Belastung durch Symptome der ORS gibt, wie es z.B. auch für Krankheitsängste [Schwind et al, 2014] und ein gestörtes Essverhalten [Davey et al, 1998] festgestellt werden konnte.…”
Section: Selbstekel Und Orsunclassified
“…Möglicherweise finden sich dysfunktionale Grundannahmen und überhöhte moralische Vorstellungen zu diesen Themen, wie etwa "Nur wenn ich gut rieche und gepflegt bin, kann ich erfolgreich sein" oder "Menschen, die nach Schweiß riechen, sind ungepflegt und asozial". Dies wäre wichtig, weil sozialer Ekel auch bei hohen moralischen Vorstellungen entstehen kann und wenn diese verletzt werden [Wagemans et al, 2018]. Auch in der Studie von Schwind et al [2014] [Davey et al, 1998;Bhikram et al, 2017].…”
Section: Diagnostische Verfahrenunclassified